ქართველური ფუძეენის დიფერენციაციის ზოგიერთი საკითხი. II - აბაშია/ Abashia, რევაზ/ Revaz (My University, 2022)
The common viewpoint in Kartvelology, which became the basis for the “Deetersian scheme” of the differentiation of the Common Kartvelian parent language, supporting the earlier separation of Svan (M. Janashvili, G. Deeters), is mainly based on the analysis of different morphological and lexical occurrences. The results of phonological and, in general, complex historical-comparative research, which are necessary for the reliable reconstruction of the ancient structural model of kindred languages, are not taken into account. At the same time, what is also important, the method of internal reconstruction is not properly used, without which it becomes almost impossible to determine the dynamics of diachronic changes of a separate language (in this case – Svan). The author believes that with the joint use of internal reconstruction and historical-comparative methods, it is possible to explain the peculiar linguistic occurrences in Svan, visibly different from Georgian and Zan. In particular, the different linguistic facts existing in Svan at the synchronic level do not in any way imply the same difference of this material at the diachronic level as compared to the data of other Kartvelian languages, since it seems that this difference is not the result of the earlier separation of Svan from the Common Kartvelian parent language, but – of the transformations carried out historically in Svan itself. As it turns out, in Svan, unlike Georgian and Zan, the phonetic changes (umlautization, affricatization, desaffricatization, spirantization...) and hence the morphological and lexical changes were so large-scale that Svan became a “specific language type”. The author believes that the Common Kartvelian parent language was initially divided into two linguistic units – Georgian and Zan-Svan – since in Zan-Svan there are occurrences that are common to them, but different from Georgian, especially – in phonology (for example, the formation of back row consonants from front row ones as a result of shifting the place of articulation...). At a later stage, Georgian still does not undergo structural changes that are very different from the Common Kartvelian parent language, and in Zan-Svan a new stage of such changes begins (vowel shifting to back in Zan, systemic phonetic changes of consonants in Svan, as well as morphological and lexical changes: simplification of auslaut in Svan, new ways of formation of passive and participle forms in Svan...), as a result of which the Zan-Svan linguistic unity breaks up into Zan (Megrelian-Laz) and Svan languages. Taking into account both the above-mentioned and other standpoints known in the Kartvelology, the author believes that the differentiation scheme of the Common Kartvelian parent language can be presented in the following form: Common Kartvelian Parent Language: Zan-Svan Zan Svan Georgian
SOME ISSUES OF THE DIFFERENTIATION OF THE COMMON KARTVELIAN PARENT LANGUAGE. II
Keywords: ქართველური ენები; ფუძეენის რეკონსტრუქცია; ქართველური ფუძეენის დიფერენციაციის სქემა; შინაგანი რეკონსტრუქციის მეთოდი; ისტორიულ-შედარებითი მეთოდი; Kartvelian languages; reconstruction of parent language; method of inner reconstruction; historical-comparative method; differentiation scheme of Common Kartvelian parent Language